(untitled) (Research, Society and Development, 2023)
The pandemic caused by the new Coronavirus (Covid-19) has been a great challenge. The presence of the Dental Surgeon (DS) in hospitals became evident. In this scenario, the study aimed to evaluate the oral care protocols during the Covid-19 pandemic in the Intensive Care Units (ICUs) of a hospital in Belo Horizonte, Minas Gerais, under the eyes of professionals in the field. This is a descriptive observational study involving the application of a questionnaire to the DS professionals and the others that compose the multidisciplinary team that work in the ICUs of the hospital from October 2021 to March 2022. The results showed a total of 153 professionals who responded to the survey being 70% female. More than 2/3 of the professionals received training to assess oral health conditions in patients hospitalized. The oral hygiene protocol used was mechanical removal of the biofilm associated with the use of 0.12% chlorhexidine digluconate. The most prevalent oral health conditions were halitosis and trauma to the lips due to prolonged use of the mechanical ventilation tube. It was observed that most professionals felt prepared to care for patients with a confirmed diagnosis of Covid-19. Even during the pandemic, the service remained attentive to care and biosafety protocols, there was a change in the oral hygiene protocol and the team was trained and adhered to the new approaches for critically ill patients affected by the new coronavirus. In addition, it was concluded that the intensive care dentist is extremely important in the multidisciplinary team.